Towards an unprotected self-activating glycosyl donor system: Bromobutyl glycosides - Davis, B; Wood, S; Maughan, M (2002)
Bromobutyl mannopyranosides have been successfully used as both protected and unprotected glycosyl donors both with and without the use of an external activator.